Karakteristik Tanah di Daerah Tanjung Kamuning Garut - Ardian Nur Rahman; Dendi Yogaswara (Jurnal Konstruksi, 2022)
Prof. KH Anwar Musaddad is located in the Garut City area, West Java Province, which is a connecting road between Banyuresmi District and Tanjung Kamuning District. Due to the large amount of damage on Jalan Prof. KH. Anwar Musaddad who set the goals for this research. The purpose of this research is to identify soil characteristics, analyze and classify soil types. The research method used is a quantitative experimental method. Tests carried out are by testing in the field and laboratory. Testing in the field, namely by sondir test and laboratory testing includes physical and mechanical properties of the soil. Testing of the physical properties of the soil includes water content, specific gravity, Atterberg limits and sieving analysis. As for testing the mechanical properties of the soil, it includes direct shear strength testing. The results obtained from this study indicate the type of soil in Jalan Pro. KH. Anwar Musaddad is a sandy soil with the USCS classification in the SP and SC groups, while the AASHTO classification is in the A-3 and A-2-7 groups.